2019
DOI: 10.1016/j.mee.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Ni/Au multilayers by electrochemistry: A crucial system in electronics - A critical review

Abstract: The deposition of various Ni alloys and Ni composite films is studied.  The deposition of different noble metal thin films is studied.  Dispersing methods of particles to make composite films are described.  The importance of post-treatment techniques on thin films is explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 261 publications
(419 reference statements)
0
7
0
Order By: Relevance
“…Besides the step-coverage, continuity, and uniformity of the electrolessly plated Ni, the chemical composition of Ni film is another crucial factor that determines its conductivity and diffusion barrier properties and hence its suitability as a seed layer. ,, Figure presents the EDX spectrum of the Ni/polymer composite, which confirms the presence of Ni peaks (at 0.742/0.762 and 0.851 keV) in addition to the elements from the underlying polymer layer (C at 0.277 keV, N at 0.392 keV, and O at 0.525 keV). A small peak of boron positioned at 0.183 keV cannot be undervalued as it is a light element ( Z = 5) and often undetectable on EDX measurements because of various inherent physical problems for the analysis of light elements with EDX (low fluorescence yield, absorption and peak overlapping with L, M, and N lines of the heavier elements.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Besides the step-coverage, continuity, and uniformity of the electrolessly plated Ni, the chemical composition of Ni film is another crucial factor that determines its conductivity and diffusion barrier properties and hence its suitability as a seed layer. ,, Figure presents the EDX spectrum of the Ni/polymer composite, which confirms the presence of Ni peaks (at 0.742/0.762 and 0.851 keV) in addition to the elements from the underlying polymer layer (C at 0.277 keV, N at 0.392 keV, and O at 0.525 keV). A small peak of boron positioned at 0.183 keV cannot be undervalued as it is a light element ( Z = 5) and often undetectable on EDX measurements because of various inherent physical problems for the analysis of light elements with EDX (low fluorescence yield, absorption and peak overlapping with L, M, and N lines of the heavier elements.…”
Section: Resultsmentioning
confidence: 83%
“…35 The literature also suggests that boron is codeposited into the coating to form a Ni alloy when a DMAB reducing agent is used 17 and affects the film properties (hardness, electric conductivity, abrasion resistance, etc.). 5,34 Our EDX observation hints at the incorporation of boron inside the Ni lattice; however, a more accurate estimation of its amount is essential to establish the usefulness of the barrier layer for copper deposition. XPS analysis of the Ar-sputtered Ni film has been reported for determining the boron amount accurately.…”
Section: Application Of a Nickel/polymer Composite For Copper Metalli...mentioning
confidence: 97%
“…Meanwhile, Cu used the defects of the Ni–P layer and Au layer to diffuse to the Au-top surface, and it was eventually oxidized there under the acceleration of a galvanic coupling with Au. 2 Murugan's research work 63 showed that the brown corrosion product was consisted of a thick base of Cu 2 O covered by a film of CuO (major) and Cu 2 (OH) 3 Cl (minor) with XPS analysis. It can be seen that the pores and gaps of the coating are closely related to corrosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…1 It is not recommended to deposit gold directly on copper, because copper will diffuse to the gold layer under the high temperature of wire bonding and encapsulation processes. 2 A nickel-phosphorus alloy can be used as a barrier to prevent diffusion. 3,4 In electronics, it is a common surface treatment to deposit nickelphosphorus alloy and gold on the copper substrate in turn.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite its extreme toxicity, cyanide is still extensively used in the gold and silver mining industry, herbicides, electroplating technology, and plastic manufacturing. [3][4][5] Therefore, salts containing cyanide ions often originate from industrial waste. 6 According to the World Health Organization (WHO), its acceptable concentration in drinking water is limited to 1.9 μM (or 200 ppb as set by USEPA).…”
Section: Introductionmentioning
confidence: 99%